FUNCTIONS AND PECULIARITIES OF MANAGEMENT OF ELECTRICAL POWER ENGINEERING COMPLEX IN THE TRANSITION PERIOD - S. B Belyi; T. G. Pospelova; P. V. Yakoubovich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2003)
The principles and peculiarities of the corporate changes in power industry on the basis of «organizational development» theory have been considered in the paper. Special attention has been given to the functions of top-management in the transition period.